Current Clinical Options for the Management of Itch in Atopic Dermatitis - Lipman ZM; Labib A; Yosipovitch G (Dove Medical Press, 2021)
Zoe M Lipman, Angelina Labib, Gil Yosipovitch Dr. Phillip Frost Department of Dermatology and Cutaneous Surgery and Miami Itch Center, University of Miami Miller School of Medicine, Miami, FL, USACorrespondence: Gil YosipovitchDr Phillip Frost Department of Dermatology and Miami Itch Center, University of Miami Hospital, 1600 NW 10th Ave RMSB Building, 2067B Tel +1 3052135824Email gyosipovitch@med.miami.eduAbstract: Pruritus is the most burdensome and prevalent symptom in patients suffering from atopic dermatitis. Treating atopic itch has historically been a challenge due to multiple underlying mechanisms within its pathogenesis and an incomplete understanding of them. In recent years, our understanding of these mechanisms have increased tremendously and subsequently, new treatments have reached the market that target the pathophysiology of atopic itch from different angles. In addition, there are several promising new treatments currently in development and trials. In the current article, we discuss these currently available treatment options, their available evidence and efficacy, and highlight some of the more recent advancements in the field.Keywords: eczema, pruritus, itch, atopic dermatitis